Tick-borne pathogens, including Crimean-Congo haemorrhagic fever virus, at livestock markets and slaughterhouses in western Kenya - Chiuya, T.; Masiga, D.K.; Falzon, Laura C.; Bastos, A.D.S.; Fèvre, Eric M.; Villinger, J. (Hindawi Limited, 2021)
Vectors of emerging infectious diseases have expanded their distributional ranges in recent decades due to increased global travel, trade connectivity, and climate change. Transboundary range shifts, arising from the continuous movement of humans and livestock across borders, are of particular disease control concern. Several tick‐borne diseases are known to circulate between eastern Uganda and the western counties of Kenya, with one fatal case of Crimean‐Congo haemorrhagic fever (CCHF) reported in 2000 in western Kenya. Recent reports of CCHF in Uganda has highlighted the risk of cross‐border disease translocation and the importance of establishing inter‐epidemic, early warning systems to detect possible outbreaks. We therefore carried out surveillance of tick‐borne zoonotic pathogens at livestock markets and slaughterhouses in three counties of western Kenya that neighbour Uganda. Ticks and other ectoparasites were collected from livestock and identified using morphological keys. The two most frequently sampled tick species were Rhipicephalus decoloratus (35%) and Amblyomma variegatum (30%); Ctenocephalides felis fleas and Haematopinus suis lice were also present. In total 486 ticks, lice, and fleas were screened for pathogen presence using established molecular workflows incorporating high‐resolution melting analysis and identified through sequencing of PCR products. We detected CCHF virus in Rh. decoloratus and Rhipicephalus sp. cattle ticks and 82 of 96 pools of Am. variegatum were positive for Rickettsia africae. Apicomplexan protozoa and bacteria of veterinary importance, such as Theileria parva, Babesia bigemina, and Anaplasma marginale, were primarily detected in rhipicephaline ticks. Our findings show the presence of several pathogens of public health and veterinary importance in ticks from livestock at livestock markets and slaughterhouses in western Kenya. Confirmation of CCHF virus, a Nairovirus that causes haemorrhagic fever with a high case fatality rate in humans highlights the risk of under‐diagnosed zoonotic diseases and calls for continuous surveillance and the development of preventative measures.